Optimization of signal peptide via site-directed mutagenesis for enhanced secretion of heterologous proteins in lactococcus lactis - Alias, Nur Aqlili Riana; Song, Adelene Ai Lian; Alitheen, Noorjahan Banu; Rahim, Raha Abdul; Othman, Siti Sarah; In, Lionel Lian Aun (MDPI AG, 2022)
Secretion efficiency of heterologous proteins in the Generally Regarded As Safe (GRAS) Lactococcus lactis is often reported to be insufficiently low due to limitations such as poor targeting and translocation by the signal peptide or degradation by the host proteases. In this study, the secretion efficiency in the host was enhanced through the utilization of a heterologous signal peptide (SP) SPK1 of Pediococcus pentosaceus. The SPK1 was subjected to site-directed mutations targeting its tripartite N-, H-, and C-domains, and the effect on secretion efficiency as compared to the wild-type SPK1 and native lactococcal USP45 was determined on a reporter nuclease (NUC) of Staphylococcus aureus. A Fluorescence Resonance Energy Transfer (FRET) analysis indicated that four out of eight SPK1 variants successfully enhanced the secretion of NUC, with the best mutant, SPKM19, showing elevated secretion efficiency up to 88% (or by 1.4-fold) and an improved secretion activity yield of 0.292 ± 0.122 U/mL (or by 1.7-fold) compared to the wild-type SPK1. Modifications of the SPK1 at the cleavage site C-domain region had successfully augmented the secretion efficiency. Meanwhile, mutations in the H-domain region had resulted in a detrimental effect on the NUC secretion. The development of heterologous SPs with better efficacy than the USP45 has been demonstrated in this study for enhanced secretion of heterologous production and mucosal delivery applications in the lactococcal host.